K.R.T Purbaningrat: Bĕdhaya sebagai Media Rekam Peristiwa - Apriastuti Rahayu, Yosephin (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2012)
Information conveyed through the history is not always recorded in writing, but also in various other media. Information about events in the past can be obtained in various ways and in various forms. K.R.T. Purbaningrat, a Kraton Yogyakarta abdidalĕm who lived during the colonial times chose a unique way to 'record' the historical events of his time. As a ‘choreographer’, K.R.T. Purbaningrat used the mystical dance bĕdhaya as a medium to record and pass on information. Sindhenan in bĕdhaya was used as well to reveal the important events surrounding the king and his kingdom. This paper wants to suggest an interpretation of a cultural dance used to record historical events. It also brings forward a challenge for contemporary history science in the discovery and interpretation of historical information sources other than writings.Keywords:informasi sejarah l K.R.T. Purbaningrat l tarian bĕdhaya lmedia rekam l KratonYogyakarta l budaya Jawa